SandRider - Sage, Angie (Sage, Angie. Todhunter moon, 2015)
Alice TodHunter Moon, now an apprentice to the ExtraOrdinary Wizard Septimus Heap, embarks on a quest with her friends Oskar and Ferdie to locate the Egg of the Orm--a source of great Magyk--before the baby Orm hatches and imprints on the evil sorcerer Oraton-Marr.